Effectiveness of Guiding Question Technique on Grade 7 Students' Writing Skills - Joseph R Casipit; Phillip G Queroda (ASEAN Multidisciplinary Research Journal, 2019)
This study determined the following, first is the socio-demographic profile of the Grade-7 students using their age, sex, religion, latest grade in English, types of media used at home and media exposure ; second is the pretest and posttest level of writing skills and scores of the Grade-7 students in composition writing before and after the exposure to guiding question technique ;  third is the relationship of the level of writing skills and their profile variables ; and lastly  difference in the writing skills of the grade 7 students before and after the exposure to guided question techniques. The subject respondents of this study were the 40 Grade-7 students taking English subject in Telbang National High School, in Alaminos City Schools Division Office of Pangasinan. The students were taught composition writing with guiding questions technique within the fourth quarter of the school year 2018-2019. This study made used the one group pre-test post-test experimental design.Moreover, this study made use of the frequency counts and percentages for the profiling of the students. Also, the minimum score, maximum score, mean, median, skewness, kurtosis, standard deviations and histogram graphs were used to describe pre-test and post-test scores of the Grade-7 students in composition writing.  In addition, Chi-square tests, and Kendalls’ tau-b analysis were utilized to determine relationship among the pre-test writing skills and profile variables and post-test writing skills and their profile variables. For effect size, Cramers V or Phi were employed. Moreover, the paired samples t-test was utilized to determine difference on the pre-test and post-test scores and the Wilcoxon test was used to test difference on the writing skills of the Grade-7 students in the pre-test – post-test composition writing. It is recommended that students should be exposed on textbooks to hone and to develop learner's competence in different language skills, especially writing.